Minor Stroke Syndromes in Large-Vessel Occlusions: Mechanical Thrombectomy or Thrombolysis Only? - Messer, M.P.; Schönenberger, S.; Möhlenbruch, M.A.; Pfaff, J.; Herweh, C.; Ringleb, P.A.; Nagel, S. (American Journal of Neuroradiology, 2017)
SUMMARY: While mechanical thrombectomy for large-vessel occlusions is now an evidence-based treatment, its efficacy and safety in minor stroke syndromes (NIHSS ≤ 5) is not proved. We identified, in our prospective data base, 378 patients with minor strokes in the anterior circulation; 54 (14.2%) of these had proved large-vessel occlusions. Eight of 54 (14.8%) were immediately treated with mechanical thrombectomy, 6/54 (11.1%) after early neurologic deterioration, and the rest were treated with standard thrombolysis only. Rates of successful recanalization were similar between the 2 mechanical thrombectomy groups (75% versus 100%). Rates of excellent outcome (modified Rankin Scale 0–1) were higher in patients with immediate thrombectomy (75%) compared with patients with delayed thrombectomy (33.3%) and thrombolysis only (55%). No symptomatic intracranial hemorrhage occurred in either group. These descriptive data are encouraging, and further analysis of large registries or even randomized controlled trials in this patient subgroup should be performed.IVintravenous thrombolysis onlyMSSminor stroke syndromeMTmechanical thrombectomyENDearly neurologic deteriorationMT-Imechanical thrombectomy immediatelysICHsymptomatic intracranial hemorrhage